2023
DOI: 10.1007/s12015-023-10610-5
|View full text |Cite
|
Sign up to set email alerts
|

WNT Signaling in Stem Cells: A Look into the Non-Canonical Pathway

Miguel Angel Sarabia-Sánchez,
Martha Robles-Flores

Abstract: Tissue homeostasis is crucial for multicellular organisms, wherein the loss of cells is compensated by generating new cells with the capacity for proliferation and differentiation. At the origin of these populations are the stem cells, which have the potential to give rise to cells with both capabilities, and persevere for a long time through the self-renewal and quiescence. Since the discovery of stem cells, an enormous effort has been focused on learning about their functions and the molecular regulation beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…35,36 In the process of normal hair growth, Wnt proteins bind to their receptors on hair follicle cells, thereby initiating the activation of the Wnt/β-catenin pathway. 37 This activation triggers the accumulation and translocation of β-catenin into the nucleus, where it effectively regulates the expression of target genes associated with hair growth and maintenance. 38 These specific genes facilitate the proliferation of hair follicle cells, extend the anagen (growth) phase of the hair cycle and inhibit both catagen (regression) and telogen (resting) phases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 In the process of normal hair growth, Wnt proteins bind to their receptors on hair follicle cells, thereby initiating the activation of the Wnt/β-catenin pathway. 37 This activation triggers the accumulation and translocation of β-catenin into the nucleus, where it effectively regulates the expression of target genes associated with hair growth and maintenance. 38 These specific genes facilitate the proliferation of hair follicle cells, extend the anagen (growth) phase of the hair cycle and inhibit both catagen (regression) and telogen (resting) phases.…”
Section: Discussionmentioning
confidence: 99%
“…In various in vitro and in vivo studies, several plant‐derived chemicals have been reported to promote hair growth by activating Wnt/β‐catenin signalling 35,36 . In the process of normal hair growth, Wnt proteins bind to their receptors on hair follicle cells, thereby initiating the activation of the Wnt/β‐catenin pathway 37 . This activation triggers the accumulation and translocation of β‐catenin into the nucleus, where it effectively regulates the expression of target genes associated with hair growth and maintenance 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The non‐canonical Wnt cascade can be further divided into the Wnt/planar cell polarity pathway and the Wnt/Ca 2+ pathway. The Wnt/Ca 2+ pathway results in the discharge of intracellular calcium and promotes calcium‐dependant mechanisms, while the Wnt/planar cell polarity pathway is responsible for the development of cell polarity, cytoskeletal re‐arrangement, cell migration and adhesion (Sánchez & Flores, 2023). Instead of LRP5/6, non‐canonical Wnt ligands (namely Wnt3a, Wnt4, Wnt5a, Wnt5b, Wnt7b, Wnt10b and Wnt16) bind to different co‐receptors like TYKs and receptor TYK‐like orphan receptor (Lojk & Marc, 2021).…”
Section: Signalling Cascades and Cellular Crosstalk In Ramentioning
confidence: 99%